PERAN GURU PAK DALAM MEMBENTUK KARAKTER KRISTIANI SISWA DI SMTK FIRDAUS JAYAPURA - Yunita Latupeirissa; Rheinhard David Sutrisno (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
ABSTRACT Christian Religious Education (CRE) teachers play a crucial role in shaping students' Christian character amid the moral and social challenges they encounter. This study aims to describe and analyze the roles of Christian Religious Education teachers in fostering students' Christian character. The study employed a qualitative approach using a descriptive method through library research. Data were collected from books, scholarly journal articles, and other relevant documents and were analyzed using content analysis. The literature synthesis revealed that the development of Christian character is a holistic process supported by the integration of five key roles of Christian Religious Education teachers: serving as role models, teaching Christian values, providing spiritual guidance and mentoring, acting as motivators and character builders, and enforcing discipline grounded in Christian love. The synthesis further indicates that the effectiveness of Christian character formation depends not only on the delivery of instructional content but also on teachers' consistency in integrating exemplary conduct, spiritual nurturing, motivation, and love-based discipline throughout the educational process. This study underscores that Christian Religious Education teachers are key agents in fostering students' Christian character; therefore, strengthening their pedagogical, professional, personal, and spiritual competencies is essential for promoting holistic Christian education. ABSTRAK Guru Pendidikan Agama Kristen (PAK) memiliki peran penting dalam membentuk karakter Kristiani siswa di tengah berbagai tantangan moral dan sosial yang dihadapi peserta didik. Penelitian ini bertujuan untuk mendeskripsikan dan menganalisis peran guru PAK dalam membentuk karakter Kristiani siswa. Penelitian menggunakan pendekatan kualitatif dengan metode deskriptif melalui studi pustaka (library research). Data diperoleh dari berbagai buku, jurnal ilmiah, dan dokumen yang relevan, kemudian dianalisis menggunakan teknik content analysis. Hasil sintesis literatur menunjukkan bahwa pembentukan karakter Kristiani merupakan proses yang bersifat holistik dan ditopang oleh keterpaduan lima peran utama guru PAK, yaitu sebagai teladan, pengajar nilai-nilai Kekristenan, pembimbing dan pembina rohani, motivator dan pembentuk karakter, serta penegak disiplin berbasis kasih. Sintesis tersebut menegaskan bahwa efektivitas pembentukan karakter tidak hanya bergantung pada penyampaian materi pembelajaran, tetapi juga pada konsistensi guru dalam mengintegrasikan keteladanan, pembinaan spiritual, motivasi, dan disiplin berlandaskan nilai-nilai Kristiani dalam proses pendidikan. Kajian ini menegaskan bahwa guru PAK merupakan aktor kunci dalam pembentukan karakter Kristiani, sehingga penguatan kompetensi pedagogis, profesional, kepribadian, dan spiritual menjadi prasyarat penting untuk mewujudkan pendidikan Kristen yang berorientasi pada pembentukan karakter secara holistik.